Measuring the size and impact of public cash support for children in cross-national perspective - Francesco Figari; Alari Paulus; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2009)
We suggest a new comprehensive measure of support given through tax-benefit systems to families with children. Using microsimulation techniques, this accounts for all provisions contingent on the presence of children, while usually only gross child/family benefits are considered. We use EUROMOD, the European Union tax-benefit microsimulation model, to quantify the support for children and analyse its impact on household incomes and child poverty for 19 countries. We find that the conventional approach underestimates on average the total amount of support for children by about one fifth. Furthermore, the differences between two measures vary considerably across countries and are, therefore, critical for cross-national comparisons.
Keywords: 330